THE ILLUSION OF EMPOWERMENT: GREEN SOCIAL WORK IN EAST KALIMANTAN'S EXTRACTIVE INDUSTRY - Aryanti Situmorang; Pipit Afrianti; Rianda Abdi; Brilliant Alievessa (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2026)
Abstract. Research examining Green Social Work (GSW) within extractive industries remains limited, particularly in understanding the relationships between Environmental, Social, and Governance (ESG), Social Impact Assessment (SIA), and indigenous governance systems. This research analyzes the application of Green Social Work (GSW) within the extractive context of East Kalimantan, Indonesia. Using a qualitative approach grounded in a critical paradigm, this study employs literature analysis and and field-based inquiry involving key informants from affected indigenous communities, village government officials, civil society actors, and extractive industry practitioners with a social work background. The data were analyzed using thematic analysis to identify patterns of governance, environmental vulnerability, and community responses. The findings reveal that the implementation of ESG and SIA in extractive governance tends to be procedural and performative, emphasizing compliance and reporting mechanisms rather than substantive community empowerment and ecological justice. Four interrelated themes emerged from the analysis: performative sustainability governance, persistent socio-ecological vulnerability, extractive dependency, and the resilience of indigenous governance systems. Despite increasing sustainability commitments, communities continue to experience environmental degradation, social vulnerability, and limited participation in decision-making processes. At the same time, indigenous governance systems, particularly Umaq and Simpuk, demonstrate important capacities for environmental stewardship and collective accountability. This study further expands Green Social Work scholarship by integrating perspectives from Political Ecology and Indigenous Governance within extractive industry settings. The article offers an analytical framework that connects Green Social Work, ESG governance, and indigenous territorial governance as a basis for advancing ecological justice and community wellbeing in extractive regions. Keyword: Green Social Work; Extractive Industries; Political Ecology; East Kalimantan; Greenwashing; Indigenous Knowledge. Abstrak. Penelitian mengenai Green Social Work (GSW) dalam konteks industri ekstraktif masih terbatas, khususnya dalam memahami hubungan antara Environmental, Social, and Governance (ESG), Social Impact Assessment (SIA), dan sistem tata kelola masyarakat adat. Penelitian ini menganalisis penerapan Green Social Work (GSW) dalam konteks industri ekstraktif di Kalimantan Timur, Indonesia. Dengan menggunakan pendekatan kualitatif yang berlandaskan paradigma kritis, penelitian ini memanfaatkan analisis literatur dan dan kajian lapangan yang melibatkan informan kunci dari masyarakat adat terdampak, pemerintah desa, aktivis masyarakat sipil, serta praktisi industri ekstraktif berlatar belakang pekerjaan sosial. Data dianalisis menggunakan analisis tematik untuk mengidentifikasi pola tata kelola, kerentanan lingkungan, dan respons masyarakat. Temuan penelitian menunjukkan bahwa implementasi ESG dan SIA dalam tata kelola industri ekstraktif cenderung bersifat prosedural dan performatif, dengan lebih menekankan pada mekanisme kepatuhan dan pelaporan dibandingkan pemberdayaan masyarakat dan keadilan ekologis yang substantif. Analisis menghasilkan empat tema yang saling berkaitan, yaitu tata kelola keberlanjutan yang performatif, kerentanan sosial-ekologis yang persisten, ketergantungan terhadap industri ekstraktif, dan resiliensi sistem tata kelola masyarakat adat. Meskipun komitmen terhadap keberlanjutan semakin meningkat, masyarakat masih menghadapi degradasi lingkungan, kerentanan sosial, dan keterbatasan partisipasi dalam proses pengambilan keputusan. Di saat yang sama, sistem tata kelola masyarakat adat, khususnya Umaq dan Simpuk, menunjukkan kapasitas penting dalam pengelolaan lingkungan dan akuntabilitas kolektif. Penelitian ini turut memperluas kajian Green Social Work dengan mengintegrasikan perspektif Ekologi Politik dan Tata Kelola Masyarakat Adat dalam konteks industri ekstraktif. Artikel ini menawarkan suatu kerangka analitis yang menghubungkan Green Social Work, tata kelola ESG, dan tata kelola wilayah adat sebagai dasar untuk mendorong keadilan ekologis dan kesejahteraan masyarakat di wilayah-wilayah ekstraktif.  Kata Kunci: Pekerjaan Sosial Hijau; Industri Ekstraktif; Ekologi Politik; Kalimantan Timur; Greenwashing; Pengetahuan Indigenus.